Citrullinated and malondialdehyde-acetaldehyde modified fibrinogen activates macrophages and promotes an aggressive synovial fibroblast phenotype in patients with rheumatoid arthritis - Aripova, Nozima; Duryee, Michael J.; England, Bryant R.; Hunter, Carlos D.; Mordeson, Jack E.; Ryan, Evan M.; Daubach, Eric C.; Romberger, Debra J.; Thiele, Geoffrey M.; Mikuls, Ted R. (Frontiers in Immunology, 2023)
Objective: Post-translational protein modifications with malondialdehyde-acetaldehyde (MAA) and citrulline (CIT) are implicated in the pathogenesis of rheumatoid arthritis (RA). Although precise mechanisms have not been elucidated, macrophage-fibroblast interactions have been proposed to play a central role in the development and progression of RA. The purpose of our study was to evaluate the downstream effects of macrophage released soluble mediators, following stimulation with fibrinogen (FIB) modified antigens, on human fibroblast-like synoviocytes (HFLS). Methods: PMA-treated U-937 monocytes (Mϕ) and macrophage-differentiated peripheral blood mononuclear cells (MP) were stimulated with FIB, FIB-MAA, FIB-CIT, or FIB-MAA-CIT. HFLS-RA cells were stimulated directly with FIB antigens or with supernatants (SN) from macrophages (Mϕ-SN or MP-SN) stimulated with FIB antigens. Genes associated with an aggressive HFLS phenotype, extracellular matrix proteins, and activated signaling pathways were evaluated. Results: HFLS-RA cells treated with Mϕ-SNFIB-CIT and Mϕ-SNFIB-MAA-CIT demonstrated significant increases in mRNA expression of genes associated with an aggressive phenotype at 24-h as compared to direct stimulation with the same antigens. Similar results were obtained using MP-SN. Cellular morphology was altered and protein expression of vimentin (p<0.0001 vs. Mϕ-SNFIB) and type II collagen (p<0.0001) were significantly increased in HFLS-RA cells treated with any of the Mϕ-SN generated following stimulation with modified antigens. Phosphorylation of JNK, Erk1/2, and Akt were increased most substantially in HFLS-RA treated with Mϕ-SNFIB-MAA-CIT (p<0.05 vs Mϕ-SNFIB). These and other data suggested the presence of PDGF-BB in Mϕ-SN. Mϕ-SNFIB-MAA-CIT contained the highest concentration of PDGF-BB (p<0.0001 vs. Mϕ-SNFIB) followed by Mϕ-SNFIB-CIT then Mϕ-SNFIB-MAA. HFLS-RA cells treated with PDGF-BB showed similar cellular morphology to the Mϕ-SN generated following stimulation with modified FIB, as well as the increased expression of vimentin, type II collagen, and the phosphorylation of JNK, Erk1/2 and Akt signaling molecules. Conclusion: Together, these findings support the hypothesis that in response to MAA-modified and/or citrullinated fibrinogen, macrophages release soluble factors including PDGF-BB that induce fibroblast activation and promote an aggressive fibroblast phenotype. These cellular responses were most robust following macrophage activation with dually modified fibrinogen, compared to single modification alone, providing novel insights into the combined role of multiple post-translational protein modifications in the development of RA.